Daya Antibakteri Ekstrak Etanol Daun Kubis (Brassica oleracea var.capitata f.alba) Terhadap Bakteri Escherichia coli Secara In Vitro - Siti Fatimah; Yuliana Prasetyaningsih; Riska Amelia (Journal of Health (JoH), 2016)
Background :. Escherichia coli is a bacteria cause of infections such as diarhea and urinary tractus infection. Antibiotic used for treatment of diarhea and urinary tractus infection include ampicilin, penicilin G, amoxicilin, chloramphenicol, tetracycline, and sulbenicin. These antibiotic are often used, but it has some side effects as well as the emergence of resistance. Treatment with minimal effects and does not cause mildew resistance continue to alternative antibacteria. Cabbage leaf is a vegetable which contains flavonoid, saponin, polifenol, and tanin that are antibacteria. The purpose of this study was to determine antibacteria effectivity ethanol extract of cabbage leaf (Brassica oleracea var.capitata f.alba) againts Escherichia coli bacteria in vitro. Method : This research is an experimental study with the method of diffusion (Kirby Bauer). Escherichia coli bacteria isolated obtained from Medical Laboratory Technology of Poltekkes Kemenkes Yogyakarta. Ethanol extract obtained through maseration extraction method and the concentration used were 60%, 70%, 80%, 80%, 90%, and 100%. Analysis of the research results in table and narration. Results : The results of inhibition zone is formed at a concentration of 60%, 70%, 80%, 90%, and 100% respectively are 11,33 mm, 12,33 mm, 13 mm, 14,33 mm, and 15 mm.). Conclusion : Ethanol extract of cabbage leaf (Brassica oleracea var.capitata f.alba) are antibacteria againts Escherichia coli bacteria with strong category in (10-20 mm).